Improving Patient Satisfaction Through Nutrition Literacy Assessment: A Pilot Study. (29th May 2020) - Marchello, Nicholas; Daley, Christine; Hu, Jinxiang; Sullivan, Debra; Gibbs, Heather
Abstract: Objectives: Nutrition literacy is the capacity to apply nutrition information to dietary choices and is associated with diet quality. Understanding patient nutrition literacy deficits may help dietitians provide a more patient-centered intervention and improve patient satisfaction with their nutrition care. This pilot study examined the effects of nutrition literacy assessments on patient satisfaction. Methods: Participants ( n = 89) were patients scheduled for an appointment with an outpatient dietitian. All participants completed the validated Nutrition Literacy Assessment Instrument (NLit) prior to their visit with a dietitian. Intervention-arm dietitians accessed patient NLit results to focus interventions towards individual nutrition literacy deficits. Control-arm dietitians did not access NLit results and provided traditional interventions. All participants returned one month later to retake the NLit and a modified version of the Consumer Assessment of Healthcare Providers and Systems (CAHPS) survey, a patient-centered satisfaction survey developed by the Agency for Healthcare Research and Quality (AHRQ). Correlations were used to examine relationships between patient satisfaction and baseline NLit scores, change in NLit scores, and randomization. Bootstrapped multiple linear regression models were used to examine relationships between patient satisfaction, changes in NLit score, and sociodemographic variables. Results: Mean patient satisfaction score for the cohort was 9.01 (10-point scale). Patient satisfaction was correlated with improvements in NLit score (Spearman's r = 0.265, P = 0.012). Partial correlations showed a positive relationship between changes in NLit score and patient satisfaction ( r = 0.302, P = 0.006) when controlling for randomization, age, sex, education, income, and ethnicity. Regression models showed a positive association between patient satisfaction and change in NLit score (adjusted r 2 = 0.087, P = 0.036). Conclusions: Improved nutrition literacy may improve patient satisfaction. Nutrition literacy assessments may aid dietitians to focus nutrition interventions, individualizing nutrition education, and improve patient satisfaction. Funding Sources: This work was supported by a CTSA grant from NCATS and the School of Health Professions.